Identifying Entity and Attributes of God: An Islamic Perspective Mengenal pasti Entiti dan Sifat-Sifat Allah: Satu Perspektif Islam - Khan, Israr Ahmad (Journal of Islam in Asia (E-ISSN 2289-8077), 2016)
Abstract Concept of Supreme Being is as old as the human history itself. But the idea of entity and attributes of that Being varies from culture to culture and religion to religion. Islam gives very vivid image of God, namely Allah in terms of His entity, attributes, and nature of relationships with the creature, including man. The Arabic word Allah denotes in English “The God”. He is Only One without any partner. He is totally unseen. He is the Creator, Sustainer, Provider, Controller of the entire universe. All that is in the earth and heavens belong to Him. Nothing is unto like Him. His power is infinite. He is as close to man as his jugular vein. He is the Most-Merciful, the Most-Beneficent. He is eternal with no beginning and end. He interacts with man and communicates to him every moment. He is Just and loves those who subscribe to justice. He has forbidden injustice for Himself as well as for man. He is Generous and commands man to interact with others generously. In order to be close to Him man has to be as kind to others as to his own self. The qualities Allah wants to see in man include sincerity, honesty, truthfulness, trustworthiness, justice, generosity, altruism, tolerance, forbearance, and fortitude. This paper deals with all these dimensions of “The God” from Islamic perspective as available in the Qur’an and the Prophetic traditions. Keywords: God, Allah, Entity, Attribute, the Qur’an, Islam. Abstrak Konsep Yang Maha Esa setua sejarah manusia itu sendiri. Tetapi idea entiti dan sifat-sifat-Nya berbeza dari budaya ke budaya dan agama ke agama. Islam memberikan imej yang sangat jelas mengenai tuhan, yaitu Allah dari segi entiti-Nya, sifat-sifat-Nya, dan perhubungan-Nya dengan makhluk, termasuk manusia. Perkataan Bahasa Arab yaitu Allah, dalam bahasa Inggerisnya menandakan “Tuhan”. Yang Hanya Satu tanpa penolong. Yang benar-benar Tersembunyi. Yang Maha Pencipta, Pemelihara, Pembekal, Pengawal seluruh alam semesta. Segala yang ada di bumi, dan langit adalah kepunyaan-Nya. Tidak ada yang sama seperti-Nya. Kuasa-Nya adalah tidak terbatas. Yang lebih dekat dengan manusia daripada urat lehernya. Yang Maha Pemurah, Yang Maha-Pengasihani. Yang kekal tanpa awal dan akhir. Yang berinteraksi dengan manusia pada setiap masa. Yang adil dan mengasihi orang-orang yang menegapkan keadilan. Yang mengharamkan kezaliman atas diri-Nya dan juga untuk manusia. Yang Maha Mulia dan memerintah hamba-Nya untuk berinteraksi dengan orang lain dengan sebaik-baiknya. Dalam usaha untuk rapatkan diri kepada-Nya, manusia mesti berbuat baik kepada yang lain seperti keatas dirinya. Sifat-sifat yang Allah mahu melihat dalam manusia adalah keikhlasan, kejujuran, kebenaran, amanah, keadilan, kemuliaan, pemurah, toleransi, kesabaran, dan ketabahan. Kajian ini berurusan dengan segala dimensi "Tuhan" dari perspektif Islam seperti yang terdapat di dalam Al-Quran dan Hadis. Kata Kunci: Tuhan, Allah, Entiti, Sifat-sifat, al-Quran, Islam.